Smart Helmet / Nur Manissa Sharfina … [et al.] - Sharfina, Nur Manissa; -, Natasha Amiera; -, Nurezzlin Natasha; Husain, Nor Azmawati; Ibrahim, Khalilah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Wearing a helmet is likely to be the same safety obligation for everyone. On the other hand, bikers would profit more from wearing a cutting-edge and revolutionary helmet. A smart helmet is an innovative concept that integrates many technologies to help riders ride more safely and enjoy the rides better. The Smart Helmet is provided with a built-in airbag with full support of the head and neck area. Another feature added is the built in LED lights or reflective stickers. These features can reduce the major head and neck injuries and riders can be easily spotted during the night rides. Furthermore, it will lower the risk of accidents and the risk of concussion can be prevented. Hence, we designed the Smart Helmet with two novel features added to increase the visibility level at night and severity of injuries in case of road crash.